(untitled) (Applied Biological Research, 2023)
Biosurfactants are amphiphilic bioactive compounds synthesized extra cellularly by various microbes from various substrates like sugar, oil and other waste materials. In present study a biosurfactant producing bacterium was isolated from clinical samples and characterized morpho biochemically. The isolated bacterium was tentatively identified as Pseudomonas sp. and evaluated for its oil degrading ability. The growth and biomass production by the bacterium was optimized using crude oil at different concentrations at variable incubation periods. The maximum growth was observed after 8 days of incubation on minimal medium containing 20% crude oil while maximum biomass (0.1 g) was noticed after 10 days incubation on basal mediumcontaining 25% crude oil. Based on Rf e biosurfactant produced was of rhaminolipid type I with he isolated bacterium can be employed in bioremediation processes.